-cosx=3x-1

Simple and best practice solution for -cosx=3x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -cosx=3x-1 equation:


Simplifying
-1cosx = 3x + -1

Reorder the terms:
-1cosx = -1 + 3x

Solving
-1cosx = -1 + 3x

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Divide each side by '-1osx'.
c = o-1s-1x-1 + -3o-1s-1

Simplifying
c = o-1s-1x-1 + -3o-1s-1

Reorder the terms:
c = -3o-1s-1 + o-1s-1x-1

See similar equations:

| 2x+4y=112 | | 2(x+1)-4(x+2)=2x-2 | | 4x-1=x+4-2x | | (x)=2x+1 | | 6x^2+(12-8a)x-16a=0 | | 30x+20=120 | | 7+12n= | | x=tln(2t)i | | (-42-4)-(-7-3)=y | | 8b^2-16b= | | 5y+9=3y-7 | | 7x-1o= | | 3y-7=5y+9 | | 15+(2-20)=y | | 3y-7=5y-9 | | 7x-10=24prove | | 6x+18=6xX+6-3 | | (3+9)-(-3+2)=y | | (-42+-4)+7+-3=y | | (-8+1)+4=y | | 1.5x+70=700 | | 8-(3+2)=t | | (-15-4)-(-2-15)=y | | q=3k+3 | | 525+.21x=585+.12x | | 3x+2=13(X+4) | | 3x+2=(x+4) | | y+9=2(x-1) | | y-8=-4(x+7) | | 3(0.9-1)-(x+0.6)=-0.2 | | x-5=20*10 | | 1/2x+3=1/3x+2 |

Equations solver categories